The role and research progress of the MET signalling pathway in targeted therapy for osteosarcoma - Su, Qilong; Hou, Jingyu; Du, Xinhui; Zhang, Fan; Zhang, Panhong; Wang, Bangmin; Yao, Weitao (Oncology Reviews, 2025)
MET, a receptor tyrosine kinase proto-oncogene and the specific receptor for hepatocyte growth factor (HGF), plays a critical role in the initiation and progression of osteosarcoma (OS) through sustained pathway activation. Aberrant activation of MET has been shown to trigger multiple downstream signalling pathways, including RAS-ERK, PI3K-AKT, and STAT3, which are essential for OS cell proliferation, invasion, differentiation, and drug resistance. In recent years, significant progress has been made in the development of small-molecule inhibitors and specific antibodies targeting MET for OS therapy. The use of combination therapy as a treatment strategy involves the use of MET inhibitors in conjunction with chemotherapy, immunotherapy, and other targeted therapies. This approach has the potential to overcome resistance and improve therapeutic efficacy. This review summarises the mechanisms of MET signalling in OS, with a focus on the progress of MET-targeted therapies and their combination with other therapeutic strategies. The study provides valuable insights into future research directions, offering novel perspectives on the role of MET as a therapeutic target in OS.